A comparison of student's errors in simple tenses. - Awang, Suryani; Jusoff, Kamaruzaman; Wan Hassan, Wan Aida; Wan Mohamed, Wan Nazihah (2011)
This study aims to analyze and compare errors made by students when using simple tenses in essay writing. The comparison was made after 6 months. The respondents of the study consisted of secondary school students from the Alpha and Beta classes and UiTM Kelantan groups which consisted of first and third diploma students from three different programmes. All respondents were asked to write an essay twice, with 6-month gap based on the same writing stimulus. In total, there were 107 essays written by respondents in each writing session, giving a grand total of 214 essays being analyzed. The results indicated an increase in errors amounting to 4.47% among students in the Alpha group but there is a reduction of 13.76% among the Beta group which was the weaker group. As for UiTM students, Diploma in Banking students showed an increase in the amount of errors by 8.2%. On contrary, Diploma in Business and Diploma in Information Management students showed a decrease in the amount by 23.79% and 3.4 %, respectively. The results of the study also indicated that there were some similarities in the types of errors made by the students.